Email spam origins: does the CAN SPAM act shift spam beyond United States jurisdiction? - Kigerl, Alex (Trends in organized crime)
Spam is the sending of bulk, commercial, unsolicited electronic marketing messages. Today email spam makes up the majority of all email sent worldwide. The CAN SPAM Act is U.S. federal legislation that was passed in response to the growing spam problem. However, cybercrime such as email spam does not respect national borders, and spam can be sent from anywhere in the world, so it is questioned whether the CAN SPAM Act simply shifted spam beyond United States jurisdiction. The present research sought to address this question by analyzing the impact that prosecutions of spammers has had on a sample of 5,490,905 spam emails sent between 1998 and 2013. Two measures of spam nation of origin, U.S. IP address and U.S. domain name among spam emails, were created to assess the possible impact that the CAN SPAM Act might have had on the nation of origin associated with spam email messages. Results suggest a possible impact, with more ongoing CAN SPAM Act trials and media attention predicting less spam associated with the United States. CAN SPAM activity appeared to have the largest impact on US domain name registrations. Implications of the findings and suggestions for future research are discussed.